Wood emissions and asthma development: Results from an experimental mouse model and a prospective cohort study. (June 2021) - Junge, Kristin M.; Buchenauer, Lisa; Elter, Elena; Butter, Katja; Kohajda, Tibor; Herberth, Gunda; Röder, Stefan; Borte, Michael; Kiess, Wieland; von Bergen, Martin; Simon, Jan C.; Rolle-Kampczyk, Ulrike E.; et al.
Graphical abstract: Highlights: VOC emissions from wood/wood products have no adverse effects on wheezing or asthma. Data from short-term, long-term and perinatal exposure in sensitized or non-sensitized mice. Verification in prospective birth cohort via BKMR mixture analyses. Abstract: Background: Increased use of renewable resources like sustainably produced wood in construction or for all sorts of long-lived products is considered to contribute to reducing society's carbon footprint. However, as a natural, biological material, wood and wood products emit specific volatile organic compounds (VOCs). Therefore, the evaluation of possible health effects due to wood emissions is of major interest. Objectives: We investigated the effects of an exposure to multiple wood-related VOCs on asthma development. Methods: A murine asthma model was used to evaluate possible allergic and inflammatory effects on the lung after short- or long-term and perinatal exposure to pinewood or oriented strand board (OSB). In addition, wood-related VOCs were measured within the German prospective mother–child cohort LINA and their joint effect on early wheezing or asthma development in children until the age of 10 was estimated by Bayesian kernel machine regression (BKMR) stratifying also for family history of atopy (FHA). Results: Our experimental data show that neither pinewood nor OSB emissions even at high total VOC levels and a long-lasting exposure period induce significant inflammatory or asthma-promoting effects in sensitized or non-sensitized mice. Moreover, an exposure during the vulnerable time window around birth was also without effect. Consistently, in our mother–child cohort LINA, an exposure to multiple wood-related VOCs during pregnancy or the first year of life was not associated with early wheezing or asthma development in children independent from their FHA. Conclusion: Our findings indicate that emissions from wood and wood products at levels commonly occurring in the living environment do not exert adverse effects concerning wheezing or asthma development.